Collateral Consequences on Children of Victims of Workplace Psychological Bullying (Mobbing): Traces in the Subjective and Family Dimension - Godoy Ponce, Patricio; Calvo, Yael Guadalupe; Luciano, Gabriela Melina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Research on mobbing or psychological harassment at work, allows us to understand that the impact of this psychosocial phenomenon exceeds the workplace and that the consequences on the health and well-being of workers have effects on family life and its dynamics. The article exposes the consequences on children, according to the experience of workers who suffered psychological harassment at work. The research is qualitative, descriptive-interpretative. Fifteen in-depth interviews were carried out, under informed consent, and the emerging categories were codified and analyzed, taking the grounded theory as a reference. Some conclusions of this case study refer to the fact that psychological harassment transcends the workplace to delve into family dynamics, and that a decrease in the registration of the needs of others, the emotional overflow or the reproduction of the violence experienced by the victims, they become questions by the children to adult social roles, the manifestation of symptoms and some form of representation of the violence suffered by their parents. The quality of the ties built in the historicity of the family group, allows the victims of psychological harassment to transit and leave the state of vulnerability.